2018
DOI: 10.1007/s11250-018-1621-8
|View full text |Cite
|
Sign up to set email alerts
|

Milk production and fatty acid profile of dairy cows grazing four grass species pastures during the rainy season in small-scale dairy systems in the highlands of Mexico

Abstract: The study evaluated small-scale dairy systems with continuous grazing of pastures based on three temperate grasses festulolium (FL), tall fescue (TF), and perennial ryegrass (RG), compared with subtropical kikuyu grass (KG). All pastures were associated with white clover (Trifolium repens L.). Twelve multiparous Holstein cows were assigned to a 4 × 4 Latin square replicated three times with 14-day experimental periods. Sampling and analyses of pastures, concentrates, and animal variables followed standard proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
1
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 28 publications
5
14
1
7
Order By: Relevance
“…Several authors (Kay et al, 2004;Morales-Almaráz et al, 2011;Vicente et al, 2017;Vieyra-Alberto et al, 2017) have stated that grazing dairy cows have higher intakes of linoleic (C18:2) and linolenic (C18:3) acids compared to confined cows due to the larger intake of these fatty acids from fresh herbage. This increases rumenic (C18:2c9t11) and vaccenic (C18:1t11) acids in milk, such as observed in Experiment 1 in milk, where PUFA content in milk was higher when cows grazed the black oat regrowth; with higher levels than reported by Plata-Reyes et al (2018), who reported a mean of 2.9 g 100 g -1 compared to 3.7-4.0 g 100 g -1 in the work herein reported.…”
Section: Fatty Acid Profile In Milksupporting
confidence: 57%
See 1 more Smart Citation
“…Several authors (Kay et al, 2004;Morales-Almaráz et al, 2011;Vicente et al, 2017;Vieyra-Alberto et al, 2017) have stated that grazing dairy cows have higher intakes of linoleic (C18:2) and linolenic (C18:3) acids compared to confined cows due to the larger intake of these fatty acids from fresh herbage. This increases rumenic (C18:2c9t11) and vaccenic (C18:1t11) acids in milk, such as observed in Experiment 1 in milk, where PUFA content in milk was higher when cows grazed the black oat regrowth; with higher levels than reported by Plata-Reyes et al (2018), who reported a mean of 2.9 g 100 g -1 compared to 3.7-4.0 g 100 g -1 in the work herein reported.…”
Section: Fatty Acid Profile In Milksupporting
confidence: 57%
“…Milk fat was extracted and methylated by methods described by Christie (1982), modified by Chouinard et al (1999). Separation and determination of methyl esters of fatty acids of herbage, commercial concentrate and milk was by gas chromatography (Clarus 500, Perkin Elmer, Waltham, Massachusetts, USA), with a capillary column 100 m × 0.25 mm × 0.2 μm (SP-2560, Supelco, Bellefonte, Pennsylvania, USA), with nitrogen as carrier gas (Plata-Reyes et al, 2018).…”
Section: Fatty Acid Profiles Of Feeds and Milkmentioning
confidence: 99%
“…Net herbage accumulation (NHA) and sward height (at the end of each experimental period) with a sliding plate grass meter followed procedures described by Plata-Reyes et al (2018). NHA estimation was from six 0.25 m 2 exclusion cages per treatment cutting to ground level with shears a 0.4 × 0.4 m quadrant.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, in the multiple 3×3 Latin squares repeated three times, simultaneous in space and time with cows nested into squares (groups), the number of observations per treatment was 9, leaving 14 degrees of freedom for the residual error term. The use of this design has proven useful for on-farm experiments (Celis-Alvarez et al, 2016;Burbano-Muñoz et al, 2018;Plata-Reyes et al, 2018).…”
Section: Concentratementioning
confidence: 99%
“…Mexico is the 14th largest milk producer in the world and the second in Latin America [5]. Furthermore, small-scale milk production farms approximately contribute 35% to marketed national milk production, own approximately 23% of the cattle inventory, and represent 78% of dairy herds in the country [6,7]. Despite the importance of the small-scale dairy system, these farms operate sub-optimally, which compromises profitability [8,9,10].…”
Section: Introductionmentioning
confidence: 99%